Student Perceptions of the Implementation of Big Data in Sinergy as Learning Optimization at the Bali Institute of Design and Business - Satrya Ramayu, I Made; Manurung, Handrean; Rachmadhan Amri, Muhammad Febrian; Mahendra, Gede Surya; Yoga Indrawan, I Putu (International Journal of Engineering, Science and Information Technology, 2024)
The current digital era is characterized by exponential data growth, presenting unprecedented opportunities and challenges in extensive data analysis. Data's increasing complexity and volume demand more efficient and effective analysis methods. In overcoming this challenge, big data technology is an innovative solution in data analysis. Semantic technology enriches the data modeling process by providing deeper context and meaning and facilitates more intuitive and accurate analysis, which is critical in managing diverse big data. The use of big data is an essential aspect of the learning system in information technology, especially at the Bali Design and Business Institute. This research aims to describe the implementation of big data on the Synergy platform as an effort to optimize learning at the Bali Design and Business Institute based on a literature review. Information technology that continues to develop has changed the learning paradigm by adopting Big Data in the context of e-learning. Synergy, as an innovative e-learning platform, has the potential to use Big Data to increase the personalization and effectiveness of learning for students. This research takes a qualitative approach by analyzing relevant literature and discussing the use of big data in education and e-learning. This literature review aims to understand how implementing Big Data can influence learning interactions, academic decision-making, and the development of adaptive learning strategies in educational environments. The literature review results show that using Big Data in e-learning can strengthen the personalization of learning, improve academic predictions, and provide deeper insight into student learning behavior. The implications of this research provide a solid theoretical basis for developing strategies for implementing Big Data at Synergy so that it can support improving the quality of learning at the Bali Institute of Design and Business.